Self-adjuvanting α-helical polypeptide simultaneously delivers neoantigen mRNAs and activates dendritic cells to eradicate tumors - Joonsu Han; Jiadiao Zhou; Abhisek Dwivedy; Tianrui Xue; Rimsha Bhatta; Yusheng Liu; Daniel Nguyen; Yang Bo; Yueji Wang; Xin Wang; Meng Xu; Matthew Berry; et al. (Proceedings of the National Academy of Sciences, 2026)
mRNA-based vaccines have demonstrated tremendous success during the era of COVID-19, but its therapeutic potential for treating cancer, especially poorly immunogenic solid tumors, remains largely underachieved. Herein, we report a class of self-adjuvanting α-helical polypeptides that can dramatically improve the antitumor efficacy of tumor neoantigen-encoding mRNAs. The α-helical polypeptides can facilitate the intracellular delivery of mRNAs into dendritic cells (DCs), simultaneously activate DCs by regulating NF-κB and IRF pathways, and improve the ability of dendritic cells to process and present mRNA-encoded neoantigens. Molecular docking and simulation results also confirm the stable complexation between mRNA and α-helical polypeptides. The conceived polyplex, upon subcutaneous administration, can migrate to the draining lymph nodes and transfect and activate DCs in the lymph nodes, resulting in superior neoantigen-specific cytotoxic T lymphocyte response in vivo. Compared to conventional lipoplexes or SM102 lipid nanoparticle-based mRNA vaccines that yield 0% tumor-free survival, the polyplex yields 83.3% and 33.3% tumor-free survival against E.G7-OVA lymphoma and 4T1 triple negative breast cancer, respectively, among the best antitumor efficacy reported to date for mRNA cancer vaccines. The polyplex also reprograms the immunosuppressive tumor microenvironment, by stimulating and enriching DCs, M1-phenotype CD86 + macrophages, and CD8 + T cells in the tumors. We also observed the upregulated expression of Programmed Death-1 (PD-1) by intratumoral CD8 + T cells and PD-L1 by 4T1 tumor cells after polyplex treatment and further demonstrated the synergistic effect between polyplex vaccine and anti-PD-1 therapy. Our polyplex system provides a facile and generalizable approach to developing robust mRNA-based cancer vaccines.